2017
DOI: 10.1002/suco.201600075
|View full text |Cite
|
Sign up to set email alerts
|

Fiber content and curing time effect on the tensile characteristics of ultra high performance fiber reinforced concrete

Abstract: Ultra high performance fiber reinforced concrete (UHPFRC) is a concrete type with superior mechanical properties and of a relatively high tensile strength. The tensile stress–strain characteristics of UHPFRC are highly affected by the mixture design and the curing regime. In this study, an extensive experimental investigation has been conducted with direct tensile tests on a number of specimens that contained different percentages of steel fibers and different cement types were applied. Also, various curing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The effect of different type, length and volume fraction of fibres on the mechanical properties of UHPFRC has been examined by a number of researchers [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Paschalis and Lampropoulos [ 5 ] found that an increase in the steel fibre content from 1 to 6 Vol.-% enhanced the tensile strength by 92% and the compressive strength by 72%.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of different type, length and volume fraction of fibres on the mechanical properties of UHPFRC has been examined by a number of researchers [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Paschalis and Lampropoulos [ 5 ] found that an increase in the steel fibre content from 1 to 6 Vol.-% enhanced the tensile strength by 92% and the compressive strength by 72%.…”
Section: Introductionmentioning
confidence: 99%
“…The use of UHPFRC could improve durability, ductility and resistance of strengthened RC structures due to its superior mechanical properties. There are several published studies on the mechanical properties of UHPFRC material …”
Section: Introductionmentioning
confidence: 99%
“…There are several published studies on the mechanical properties of UHPFRC material. [8][9][10][11][12][13][14][15][16][17] Paschalis and Lampropoulos 8 investigated the effect of fiber content, cement type and curing time on the tensile and compressive characteristics of UHPFRC material. Results showed that use of 52.5 N type I cement instead of 32.5 R type II cement resulted in 18% higher tensile strength and 16% higher compressive strength.…”
mentioning
confidence: 99%
“…In this study, different parameters which affect the strength and the workability of UHPFRC have been investigated and an optimum mixture design was proposed. Paschalis and Lampropoulos (2017), investigated the tensile characteristics of UHPFRP for different curing regimes and different fiber contents. Based on the results, different stress-strain models for the different fiber contents have been proposed, while an optimum curing period for the UHPFRC has been suggested.…”
Section: Introductionmentioning
confidence: 99%